Homoeopathy and Autism Spectrum Disorder: A Holistic Approach to Symptom Management (Homoeopathy for All, 2025)
Autism spectrum disorder (ASD)  is a set of neurodevelopmental  disorders characterised by a deficit  in social behaviours and nonverbal  interactions, such as reduced eye  contact, facial expression, and body  gestures, in the first 3 years of life.  It is not a single disorder, but rather  a multi-factorial condition resulting  from the interaction of genetic and  non-genetic risk factors. Autism Spectrum Disorder  is a multifaceted condition  requiring early, comprehensive,  and sustained intervention. While  conventional approaches emphasise  behaviour modification and  pharmacotherapy for associated  symptoms, homoeopathy offers a  promising complementary role with  individualised remedies addressing  the child’s mental, emotional,  and physical constitution. Future  research should focus on integrating  evidence-based alternative therapies  with conventional modalities to  improve the quality of life for  individuals affected and their  families.
Keywords: Autism, ASD, Homoeopathy, Developmental disorders